(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Nowadays, an enterprise cannot function effectively or make informed business decisions without access to and use of business data. Business data provides information that supports strategic decision-making for entrepreneurs and all other employees within the organization. Therefore, this paper aims to demonstrate how strategically defining information requirements, and subsequently database modelling, supports business operations. Accordingly, the research methodology for this paper involves analysing a case study focusing on a specific fire department. Through the case study, the information requirements are identified and used to create a database model. Based on the modelling and creation of the database, the identified information requirements are analysed and discussed in the context of operational improvements for the firefighting station.